2010
DOI: 10.1145/1778765.1778793
|View full text |Cite
|
Sign up to set email alerts
|

An artist friendly hair shading system

Abstract: Rendering hair in motion pictures is an important and challenging task. Despite much research on physically based hair rendering, it is currently difficult to benefit from this work because physically based shading models do not offer artist friendly controls. As a consequence much production work so far has used ad hoc shaders that are easier to control, but often lack the richness seen in real hair. We show that physically based shading models fail to provide intuitive artist controls and we introduce a nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…One of the very few publications concerned with the design of user interfaces for shaders is the work by Sadeghi et al (Sadeghi et al, 2010), who identified three requirements for artist-friendly control parameters:…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the very few publications concerned with the design of user interfaces for shaders is the work by Sadeghi et al (Sadeghi et al, 2010), who identified three requirements for artist-friendly control parameters:…”
Section: Related Workmentioning
confidence: 99%
“…Based on these principles, we extended the three principles proposed by Sadeghi et al (Sadeghi et al, 2010) and include three additional principles. Thus, our six principles for the user-centered design of interfaces to control parameters of shaders are:…”
Section: Principles Of User-centered Design Of Shader Interfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…The methods for 3-D simulation of pile include the geometric modeling and texture generating. Csuri, [4] Neulander, [5] Sadeghi, [6] and Yan [7] drew the animal furs very clearly with the geometric method, but it was time-consuming and mostly used for offline rendering for film production and animation. Kajiya [8] plotted furs with three-dimensional texture generating method, and the plotted fur was very real and soft, but the early methods were not efficient in simulating knitting products.…”
Section: Introductionmentioning
confidence: 99%